Analisis standar rata-rata profitabilitas pada industri energi dan industri finansial - Sri Suryaningsum; Dyah Ayusulistyaningrum (Department of Accounting Universitas PGRI Yogyakarta, 2024)
ROA and ROE are indicators of management performance. However, there is a phenomenon in which companies exhibit different characteristics, particularly across industrial sectors. This raises concerns about the standards for what constitutes good or bad performance for companies in the energy and financial industries, given the same or different ROA and ROE values. This research aims to determine the average standard ROA and ROE values between the energy and financial sectors. This research uses ROA and ROE data from 36 companies in the energy sector and 41 companies in the financial industry, sourced from the IDX and Yahoo Finance. ROA and ROE values are secondary data to be analyzed using descriptive statistics and the homogeneity of variance. As a result, the average ROA in the Indonesian energy industry is 8.11%, while the average ROE is 16.91%. In the Indonesian financial sector, the average ROA is 1.66%, and the average ROE is 6.00%.